The Effectiveness of Rehabilitation Interventions on Pain and Disability for Complex Regional Pain Syndrome: A Systematic Review and Meta-analysis. Issue 2 (17th January 2023) - Shafiee, Erfan; MacDermid, Joy; Packham, Tara; Walton, David; Grewal, Ruby; Farzad, Maryam
Abstract : Objectives: To summarize and critically appraise the body of evidence on conservative management of complex regional pain syndrome (CRPS), we conducted a systematic review and meta-analysis of randomized controlled trials (RCTs). Methods: We conducted a literature search from inception to November 2021 in the following databases: Embase, Medline, CINAHL, Google Scholar, PEDRO, and Psychinfo. Two independent reviewers conducted risk of bias and quality assessment. Qualitative synthesis and meta-analysis were the methods for summarizing the findings of the RCTs. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach was used to rate the overall quality and certainty of the evidence on each treatment outcome. Result: Through a database search, 751 records were found, and 33 RCTs were eligible for inclusion. Studies were published between 1995 and 2021. The overall risk of bias for 2 studies was low, 8 studies were unclear, and 23 studies were high. Low-quality evidence suggests that mirror therapy (as an addition to conventional stroke rehabilitation interventions) and graded motor imagery program (compared with routine rehabilitation interventions) may result in a large improvement in pain and disability up to 6-month follow-up in poststroke CRPS-1 patients. Low-quality evidence suggests that pain exposure therapy and aerobic exercises as an additive treatment to physical therapy interventions may result in a large improvement in pain up to a 6-month follow-up. The evidence is very uncertain about the effect of all other targeted interventions over conventional physical therapy or sham treatments on pain and disability. Discussion: There is an ongoing need for high-quality studies to inform conservative management choices in CRPS.